4(5k-5)+19=-9+2(3k-8)

Simple and best practice solution for 4(5k-5)+19=-9+2(3k-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(5k-5)+19=-9+2(3k-8) equation:


Simplifying
4(5k + -5) + 19 = -9 + 2(3k + -8)

Reorder the terms:
4(-5 + 5k) + 19 = -9 + 2(3k + -8)
(-5 * 4 + 5k * 4) + 19 = -9 + 2(3k + -8)
(-20 + 20k) + 19 = -9 + 2(3k + -8)

Reorder the terms:
-20 + 19 + 20k = -9 + 2(3k + -8)

Combine like terms: -20 + 19 = -1
-1 + 20k = -9 + 2(3k + -8)

Reorder the terms:
-1 + 20k = -9 + 2(-8 + 3k)
-1 + 20k = -9 + (-8 * 2 + 3k * 2)
-1 + 20k = -9 + (-16 + 6k)

Combine like terms: -9 + -16 = -25
-1 + 20k = -25 + 6k

Solving
-1 + 20k = -25 + 6k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-6k' to each side of the equation.
-1 + 20k + -6k = -25 + 6k + -6k

Combine like terms: 20k + -6k = 14k
-1 + 14k = -25 + 6k + -6k

Combine like terms: 6k + -6k = 0
-1 + 14k = -25 + 0
-1 + 14k = -25

Add '1' to each side of the equation.
-1 + 1 + 14k = -25 + 1

Combine like terms: -1 + 1 = 0
0 + 14k = -25 + 1
14k = -25 + 1

Combine like terms: -25 + 1 = -24
14k = -24

Divide each side by '14'.
k = -1.714285714

Simplifying
k = -1.714285714

See similar equations:

| 13+3(2x-5)=1-2(3-6x) | | 3c-1c+40=34 | | 4/3+2=6 | | x+2x+13=70 | | 7.5-(-2.5)= | | a(c-2)+3(c-2)= | | 92=-8+25m | | x+.05x=23.63 | | -(5+2x)=2(3+4x) | | 5t-14=8t+4 | | 3(n-5)=9-n | | 2x+4=-1(7x+6) | | 1(5+2x)=2(3+4x) | | 8y-8=64 | | 5y/6-23=7 | | 350x23/20x7/25 | | 5t-1=24 | | 3.0-(-5.3)= | | 5+X+X=1+4X | | x+.06x=22.64 | | 4x+6+x=3+2x-3 | | x+4(x+1)=47 | | 2t-5=29 | | 2(3n-4)=-26+3n | | 2x+61=3x-8 | | -11=4u+5 | | 5y-16=49 | | 3+1.5(z+2)=3.5z-2 | | 3+7d=-4 | | -5r+36=-7(8+4r) | | 3(c-6)=10+2c | | 0.03(2c-50)=-0.6(c-3) |

Equations solver categories